Cauda equina syndrome due to primary extraskeletal Ewing’s sarcoma: a diagnostic challenge (BIRDEM Medical Journal, 2024)
Ewing’s sarcoma causing cauda equina syndrome is a rare entity. We report case history of a 20-year-old man who presented with features of cauda equine syndrome preceded by 4-month history of pain in the buttock and tip of the coccyx. Magnetic resonance imaging revealed a lesion within the spinal canal at S1–5 level and a large lobulated heterogeneously enhancing mass lesion in pelvic cavity in sacral region. Excisional biopsy revealed Ewing’s sarcoma by characteristic features on histologic analysis and immunohistochemistry. Patient was referred to oncologist for combined chemotherapy with radiotherapy.BIRDEM Med J 2024; 14(2): 99-102